Applied Linear Algebra in Action - Katsikis, Vasilios N. (IntechOpen, 2016)
The present text book contains a collection of six high-quality articles. In particular, this book is devoted to Linear Mathematics by presenting problems in Applied Linear Algebra of general or special interest.